Establishment of an experimental system to analyse extracellular vesicles during apoplastic fungal pathogenesis - Nathaniel Hearfield; Dominik Brotherton; Zedi Gao; Jameel Inal; Henrik U. Stotz (Journal of Extracellular Biology)
Abstract Phoma stem canker disease of oilseed rape (Brassica napus) is caused by the extracellular fungal pathogen Leptosphaeria maculans. Although this pathogen resides exclusively in apoplastic spaces surrounding plant cells, the significance of extracellular vesicles (EVs) has not been assessed. Here, we show a method to collect apoplastic fluids (AFs) from infected leaves or cotyledons for collection of EVs during the process of host colonisation. The 15,000 × g supernatants of AFs were shown to contain ribulose‐bisphosphate carboxylase (RuBisCO) at 7 days post‐inoculation with L. maculans, a protein that was absent from unchallenged cotyledons. RuBisCO release coincided with the switch from biotrophy to necrotrophy, suggesting the involvement of host cell death. However, RuBisCO release did not differ between compatible and incompatible interactions, suggesting necrotrophic host cell death might not be the only process involved. EVs were also collected from axenic fungal cultures and characterised for their particle size distribution using nanoparticle tracking analysis and transmission electron microscopy. The protein composition of EV‐enriched fractions was analysed using SDS‐PAGE and proteomics. Enrichment analysis of gene ontology terms provided evidence for involvement of glucan and chitin metabolism as well as catalase and peptidase activities. Most of the proteins identified have previously been found in EV studies and/or EV databases, and for most of the proteins evidence was found for an involvement in pathogenicity/virulence.